Tradisi Ketumpangan dalam Hajatan Perspektif Fiqih Muammalah: Studi Kasus di Desa Lumbangrejo Kecamatan Prigen, Kabupaten Pasuruan, Jawa Timur: Indonesia - Ahmad Luthvan Habiburrahman; Roibin; Noer Yasin (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Indonesia is a country rich in tradition, one of the traditions that runs in the midst of Indonesian society is the tradition of Ketumpangan in celebration. This tradition is commonly known as Buwuh. The tradition of Ketumpangan is a tradition of returning favours to ṣāḥib al-ḥājah, in return for the assistance received, whether in the form of goods or money. This tradition that runs in the community sometimes causes conflict, this is inseparable from differences in people's views about the tradition, shifting the meaning of this tradition and the absence of a contract. This research was conducted with the aim of knowing the practice of the Ketumpangan tradition in the celebration that runs in Lumbangrejo Village, Prigen Subdistrict, Pasuruan Regency, where later the practice of this tradition is reviewed from the perspective of Fiqh Muammalah. This type of research is qualitative research in the form of a case study with a phenomenological approach conducted in Lumbangrejo Village, Prigen District, Pasuruan Regency. Primary data sources were obtained from unstructured interviews with Ketumpangan actors, religious leaders, and cultural experts to obtain information about the practice procedures of the Ketumpangan tradition. Secondary data were obtained from scientific literature related to this research, and various literature references related to the Ketumpangan tradition. The results showed that, First, the Ketumpangan tradition in celebrations that took place in Lumbangrejo Village was based on a sense of harmony between communities, this tradition had a gradual flow starting from planning the event and giving the object of ketumpangan in stages. Second, the Ketumpangan tradition in the celebration that takes place in Lumbangrejo Village is in accordance with the grant contract in fiqh muammalah, both in terms of the pillars or conditions. Keywords: Tradition, Ketumpangan, Hibah